Seize the Day or Save the World? The Importance of Ethical Claims and Product Nature Congruity - Herédia-Colaço, Vera (Journal of business ethics, 2018)
Consumers have shown increasing interest in products that reflect social and environmental concerns—so-called “sustainable products.” Although consumers typically view sustainability positively, the ethical attributes of products do not always drive their preferences, which implies a trade-off between ethical attributes and other valued attributes. In the current research, we examine how consumers implicitly judge products and services that are more or less congruent with social and environmental concerns and how incongruity between ethical claims and a product’s nature may influence consumers to behave responsibly. The results from two experimental studies show that increasing the strength of ethical claims impairs sophisticated products’ evaluation but enhances simple products’ evaluation. Additionally, the findings reveal that the strength of ethicality on sophisticated products may impair perceptions of product enjoyment to a point at which products are evaluated more favorably when less-ethical claims are used to promote them. For managers, the results highlight an important business consideration, as they reveal the circumstances under which it is worth emphasizing the strength of the sustainability appeal of products or services. Results show that not all consumers are willing to sacrifice taste or quality in their leisure time preferring to seize the day rather than saving the world.